Síntese de derivados Chalconas e Bichalconas com avaliação da atividade Leishmanicida e antitumoral - Leite, Fernando Ferreira (2024)
Chalcones are a class of compounds generated by the secondary metabolism of plants. Previous studies have reported the range of pharmacological activities presented by these compounds, among which the leishmanicidal, anticancer, antimicrobial and antioxidant properties stand out. In this work, we aimed to synthesize novel chalcones and chalcone dimers with economically viable routes, structurally elucidate the compounds by 1H and 13C NMR spectroscopic techniques, in addition to mass spectrometry and evaluate the properties of these compounds against Leishmania infantum and Leishmania brasiliensis species, and also report anticancer properties of chalcones in studies reported in the last five years, covering the period from 2019 to 2023. Different concentrations of the compounds were evaluated against promastigote and amastigote forms of L. infantum and L. brasiliensis, showing promising inhibitions with IC50 of 10.96 and 13.64 μm. In silico studies were performed with enzymes important in the survival and maintenance of the parasite, among them trypanothione reductase and 14-αdemethylase (CYP-51). Molecular docking revealed strong interactions of the compounds with these targets, with MolDock score values lower than those of the cocrystallized ligands, ranging from -94.0758 (for CYP-51) to -50.5692 (for trypanothione reductase) of negative energy. Our findings reinforce the potential of this class of secondary metabolites and encourage further studies to discover the real mechanism of action by in vitro analysis, in addition to finding new, even more promising analogues for this still neglected disease. For a better understanding of the reader, the work was divided into 4 chapters, where in chapter 1 we address the synthesis and characterization steps of the compounds, followed by the published works, encompassing chapters 2, 3 and 4.